An event study analysing the impact of the September 11th terrorist attack, 2011 UBS rogue trading scandal and 2004 Indonesian tsunami on financial institutions. - Visholm, Boyd (2013)
This paper investigates the impact that three events had on the value of financial institutions. The three events investigated were the September 11th terrorist attack on the World Trade Center, the UBS rogue trading scandal announced in 2011 and the Indonesian tsunami that took place in 2004. The financial institutions used in my study are listed in London, New York and on the Tokyo Stock Exchange. The paper follows an event study methodology and uses the Market Model to calculate normal returns. These normal returns are subtracted from the actual return to calculate abnormal return. 10-day cumulative abnormal returns are calculated for each financial institution in the sample. In addition, the cumulative abnormal returns are aggregated to calculate the cumulative average abnormal return for each of the stock exchanges. The t-statistic is used to determine the significance of these returns. The results demonstrate that September 11th had a significant impact on the value of financial institutions listed in London. There are a number of interpretations of this with the most obvious being that banks are at the centre of the economy, so when the economy receives a major shock, their value is decreased. The key finding from the rogue trading scandal was that it caused a statistically significant increase in returns for institutions listed in London over the 10-day event window. This result is deemed to be due to the damage caused to the reputation of the institution where the fraud took place. In turn, this lead to investors purchasing the stock of other financial institutions. The results found no evidence that financial institutions stock value was impacted by the Indonesian tsunami. This study may be of particular interest to traders, policymakers and the financial institutions themselves.